Human Pressures and Impacts on Shallow Seafloor Environments of the Northern Baltic Sea - Sahla, Matti (fi=Turun yliopisto|en=University of Turku|, 2022)
ABSTRACT Unsustainable use of coastal resources and space has resulted in global degradation of marine environments. Stopping adverse development requires improved understanding of how different human activities affect nature. International treaties and national legislation have been established to stop widespread environmental deterioration, but targeted local actions are still needed. Comprehensive planning processes such as marine spatial planning (MSP) and integrated coastal zone management (ICZM), promote sustainable development of coastal regions and additionally require evaluation of human influence on the marine environment. In this thesis, I examine human pressures and impacts on the shallow seafloor environments of the northern Baltic Sea. The general aim of this work is to improve the quality of location-based human pressure and impact evaluations on marine environments. The work contributes to developing environmentally conscious coastal planning by improving knowledge and introducing new methodological solutions for pressure and impact evaluations. A great variety of spatial data has been used in this work, ranging from LiDAR point clouds to species-specific monitoring data. The analysis processes in the research utilizes and combines methodologies of scenario assessments, spatial modeling and statistical examination with a geographical approach. The results of this study display the possibilities and uncertainties of detailed remote sensing data, categorized biotope data and different modeling approaches when evaluating human pressures and impacts on shallow seafloor environments. This thesis also discusses the possibilities for utilizing open source data on benthic environments and human activities to support sustainable planning decisions. The work also reveals large-scale degradation of benthic keystone species Fucus spp. in the Finnish coastal areas using modeling and species monitoring data. The main findings of this thesis provide new geographical insights on human pressure and impact evaluations that can promote sustainable planning decisions in coastal regions. KEYWORDS: human pressure, human impact, benthic communities, Baltic Sea, maarine spatial planning, coastal planning, spatial modeling

TIIVISTELMÄ Rannikkoalueiden ja rannikon resurssien kestämätön käyttö on heikentänyt meriympäristöjen tilaa maailmanlaajuisesti. Kehityksen suunnan kääntäminen edellyttää luotettavaa tietoa ihmisen toiminnasta sekä sen vaikutuksista rannikoiden luontoon. Vaikka kansainväliset sopimukset ja kansalliset lait pyrkivät osaltaan estämään luonnon tilan heikkenemistä, niiden lisäksi tarvitaan paikallisia toimia. Esimerkiksi laaja-alaiset rannikoilla tehtävät suunnitteluprosessit, kuten merialuesuunnittelu (MSP) ja rannikkoalueiden yhdennetty käyttö ja hoito (ICZM), tavoittelevat kestävää kehitystä, mutta niiden tulee pohjautua luotettavaan tutkimustietoon. Tutkin väitöskirjassani ihmistoiminnan aiheuttamia paineita ja niiden vaikutuksia pohjoisen Itämeren mataliin merenpohjaympäristöihin. Tavoitteenani on parantaa näitä ympäristöjä kuvaavien alueellisten ihmistoimintaan kytkeytyvien paine- ja vaikutusarviointien laatua ja siten tukea matalien merenpohjaympäristöjen erityispiirteet huomioivaa rannikkosuunnittelua. Käytän tutkimuksissani monipuolisia paikkatietoaineistoja LiDAR –pistepilvistä yksittäisten lajien seurantaaineistoihin. Teen monen tyyppisiä maantieteellisiä analyyseja hyödyntäen ja yhdistellen erilaisia skenaariomenetelmiä, alueellisia paikkatietomalleja ja tilastollisia menetelmiä. Tutkimukseni tulokset osoittavat yhtäältä yksityiskohtaisten kaukokartoitusaineistojen, luokiteltujen biotooppiaineistojen ja erilaisten mallinnusmenetelmien arvon keskeisinä merenpohjien tilaa käsittelevän tiedon lähteinä, mutta tuovat esille myös niiden käyttöön liittyviä epävarmuuksia. Työssä tarkastelen erityisesti, miten avoimia tietolähteitä voidaan hyödyntää rannikon kestävän käytön suunnittelussa. Käytän myös mallinnusmenetelmiä ja lajitasoista seurantatietoa osoittaakseni rakkohaurujen (Fucus spp.) taantuneen laaja-alaisesti Suomen rannikkoalueilla. Väitöskirjani keskeisenä tuloksena on, että maantieteellinen lähestymistapa ja alueellinen työskentelymenetelmä vahvistavat rannikkoalueiden kestävää käyttöä ja suunnittelua tukevaa tietopohjaa. ASIASANAT: ihmistoiminnan paine, ihmistoiminnan vaikutus, merenpohjan yhteisöt, Itämeri, merialuesuunnittelu, rannikkosuunnittelu, levinneisyysmallinnus